Clinical review of alkalization therapy in cancer treatment - Hamaguchi, Reo; Isowa, Masahide; Narui, Ryoko; Morikawa, Hiromasa; Wada, Hiromi (Frontiers in Oncology, 2022)
One of the most unique characteristics of cancer metabolism is activated aerobic glycolysis, which is called the “Warburg effect”, and is a hallmark of cancer. An acidic tumor microenvironment (TME) resulting from activated anaerobic glycolysis is associated with cancer progression, multi-drug resistance, and immune escape. Several in vitro and in vivo studies reported that neutralization of the acidic TME by alkalizing agents, such as bicarbonate, resulted in the suppression of cancer progression and a potential benefit for anti-cancer drug responses. In clinical settings, alkalizing effects were achieved not only by alkalizing agents, but also by a following a particular diet. An epidemiological study demonstrated that more fruits and vegetables and less meat and dairy products are associated with an increase in urine pH, which may reflect the alkalizing effect on the body. However, it remains unclear whether alkaline dietary intervention improves the effects of cancer treatment. Moreover, there are few clinical reports to date regarding cancer treatments being performed on patients together with alkalization therapy. In this review, we investigated whether alkalization therapy, which includes an alkaline diet and/or alkalizing agents, improves cancer treatment.